Properties of perovskite ferroelectrics deposited on F doped SnO2 electrodes and the prospect of their integration into perovskite solar cells. (5th December 2017) - Pintilie, I.; Stancu, V.; Tomulescu, A.; Radu, R.; Besleaga Stan, C.; Trinca, L.; Pintilie, L.
Abstract: The integration of ferroelectrics in perovskite solar cells is proposed as possible way to enhance charge collection efficiency. First results on solar cell manufactured with PbTiO3 (PTO) instead of TiO2 have shown negligible values for the power conversion efficiency (PCE). This is explained by the high serial resistance of sol-gel deposited PTO on F:SnO2 electrodes (FTO). Although PTO layer has remnant polarization of 22 μC/cm 2, the high potential barrier (0.25 ± 0.05 eV) at the FTO/PTO interface and low carrier mobility (10 − 8  cm 2  V − 1  s − 1 ) compared to TiO2 leads to high serial resistance. Better results were obtained with thinner PTO layers grown by pulsed laser deposition, with PCE values up to 0.6%. Further enhancement was obtained by replacing PTO with BaTiO3 (BTO), with PCE value reaching about 0.8% after poling the cell with + 3 V. The most important finding was that the magnitude of the short circuit current increases with the amplitude of the poling voltage while the value of the open-circuit voltage remains about the same, around 0.9 V. This is explained through more efficient collection of the charges generated under illumination in the absorber layer due to the polarization that is present in the ferroelectric film. Graphical abstract: Highlights: Novel perovskite solar cells were fabricated by replacing the TiO2 layer with PbTiO3 and BaTiO3 perovskite ferroelectrics Power conversion efficiency of nearly 1% was obtained by lowering the serial resistance of the ferroelectric layer Short-circuit current increases with the magnitude of the ferroelectric polarization oriented towards the FTO electrode